Automated Negative Lightning Return Strokes Characterization Using Brute-Force Search Algorithm - Faranadia Abdul Haris; Mohd Zainal Abidin Ab. Kadir; Sukhairi Sudin; Jasronita Jasni; Dalina Johari; Nur Hazirah Zaini (Pertanika Journal of Science & Technology, 2024)
Indexed by WOS/ERA/MYCITE